The influence of obesity on severe Covid-19 (Research, Society and Development, 2021)
Obesity is defined as the excess accumulation of adipose tissue, and its quantity is harmful to health. In addition to being an aggravating factor for multiple comorbidities, it can also lead to serious metabolic and respiratory diseases. Its etiology is very complex and has multifactorial characteristics. The work aims to expose through the analysis of scientific articles the influence of obesity in severe Covid-19. This is a literature review of a qualitative nature based on scientific production based on studies already published between the years 2019 to 2021. Concerning international data show that the frequency of obesity is very high among critically ill patients receiving intensive care of SARS-CoV-2. In Brazil, obesity is the main comorbidity associated with death in children under 60 years of age. Obese people are four times more at risk of injury and death from COVID-19. Research using clinical and epidemiological protocols is needed to determine the relationship between overweight, obesity and increased risk of complications from COVID-19, in order to generate and establish a deeper and better understanding of this association, including an understanding of complications of overweight patients.